Composite proton exchange membrane and preparation method thereof
By introducing the aramid nano -fiber in the proton exchange film and adopting papermaking method to prepare a composite layer to form a composite proton exchange membrane with a layered structure, it solves the problem of insufficient conductivity of the existing proton exchange membrane, and achieves higher higher Thermal stability, mechanical strength and anti -oligability.
Patent Information
- Application Number
- CN202411429936.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-28
AI Technical Summary
While improving mechanical stability and reducing methanol permeability, the existing proton exchange membrane fails to effectively improve proton conductivity, limiting its practical application in fuel cells.
By introducing the aramid nano -fiber in the proton exchange film, the papermaking method is used to prepare a composite layer, and then the full fluorosulfonic acid solution is coated on both sides of the composite layer to form a composite proton exchange membrane with a layered structure.
Under the premise of ensuring high proton conduction rates, the thermal stability, size stability, mechanical strength, and anti -exploitability of the proton exchange membrane are improved, and the hydrogen transmission rate is reduced.
Smart Images

Figure BDA0005083365380000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery separators, and in particular relates to a composite proton exchange membrane and a preparation method thereof. Background Art
[0002] At present, the resources of traditional fossil fuels are obviously reduced, and the problem of environmental pollution is becoming increasingly serious. The development and utilization of renewable resources has become an important issue facing the sustainable economic development of various countries and a strategic research direction for the future development of countries around the world. Fuel cells (FCs) are devices that convert chemical energy into electrical energy through chemical reactions. The theoretical conversion rate is as high as 83%, and they have the advantages of safety and environmental protection, which have attracted widespread attention from researchers. The operating temperature of proton exchange membrane fuel cells (PEMFC) is relatively low, at 70-80℃, and they have the advantages of no pollution, high efficiency and light weight. PEMFC uses hydrogen as fuel and produces water. The power generation process does not involve hydrogen and oxygen combustion, so it is not restricted by the Carnot cycle. Its energy conversion rate is as high as 60%, and it is known as an efficient, clean and green environmentally friendly battery. As the core component of PEMFC, the performance of proton exchange membrane (PEM) is increasingly difficult to meet the requirements of batteries, such as the balance between its conductivity, swelling and mechanical properties. The currently used perfluorosulfonic acid proton exchange membrane (Nafion) has a high hydrogen permeability and large water swelling, which cannot give full play to the performance advantages of direct fuel cells. Therefore, more and more research is devoted to the development of fluorinated or non-fluorinated proton exchange membranes.
[0003] The invention patent with publication number CN104558649A discloses a PVDF-modified perfluorosulfonic acid proton exchange membrane and its preparation method. The invention uniformly compounds PVDF into the perfluorosulfonic acid proton exchange membrane by ammonia cross-linking. The PVDF-modified perfluorosulfonic acid proton exchange membrane prepared in this way effectively improves the mechanical stability and dimensional stability of the composite proton exchange membrane and reduces the methanol permeability. However, the invention does not greatly improve the proton conductivity, which limits the practical application of the composite proton exchange membrane. Summary of the invention
[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a composite proton exchange membrane.
[0005] Another object of the present invention is to provide a method for preparing the composite proton exchange membrane.
[0006] The purpose of the present invention is achieved through the following technical solutions.
[0007] A composite proton exchange membrane has a layered structure, which comprises an upper layer, a middle layer and a lower layer from top to bottom. The upper layer comprises perfluorosulfonic acid (PFSA), the middle layer comprises para-aramid nanofibers and perfluorosulfonic acid, and the lower layer comprises perfluorosulfonic acid (PFSA).
[0008] In the above technical solution, the thickness of the composite proton exchange membrane is 20 to 60 μm.
[0009] In the above technical solution, the thickness of the middle layer is 15-30 μm, the thickness of the upper layer is 5-10 μm, and the thickness of the lower layer is 5-10 μm.
[0010] In the above technical solution, the ratio of the para-aramid nanofibers to the perfluorosulfonic acid in the middle layer is (0.1-5.0): (0.04-2.0) by mass.
[0011] In the above technical solution, the areas of the upper layer, the middle layer and the lower layer are the same.
[0012] The method for preparing the composite proton exchange membrane comprises the following steps:
[0013] Step 1, under stirring conditions, mixing a para-aramid nanofiber slurry and a perfluorosulfonic acid solution until uniform, to obtain a composite solution, wherein the para-aramid nanofiber slurry includes para-aramid nanofibers, the perfluorosulfonic acid solution includes perfluorosulfonic acid, and the ratio of the para-aramid nanofibers in the para-aramid nanofiber slurry to the perfluorosulfonic acid in the perfluorosulfonic acid solution is (0.1-5.0): (0.04-2.0) by weight;
[0014] In step 1, the para-aramid nanofiber slurry contains 0.01 to 10 wt % of the para-aramid nanofiber.
[0015] In step 1, the para-aramid nanofiber slurry further includes water.
[0016] In step 1, the content of perfluorosulfonic acid in the perfluorosulfonic acid solution is 3-6 wt %.
[0017] In step 1, the stirring speed is 300-800 r / min.
[0018] In step 1, the method for obtaining para-aramid nanofiber slurry comprises the following steps:
[0019] S1, mixing a para-aramid polymer (poly(p-phenylene terephthalamide, PPTA)) and a coagulant, stirring, to obtain a para-aramid nanofiber dispersion containing para-aramid nanofibers, wherein the ratio of the para-aramid polymer to the coagulant is 1:(2-10) by weight, the coagulant is a first substance, a second substance or water, the second substance is a mixture of water and the first substance, and the first substance is N-methylpyrrolidone, methanol and / or ethanol;
[0020] In S1, the stirring speed is 300-1000 r / min, and the stirring time is 0.5-3 h.
[0021] S2, washing the para-aramid nanofibers, and dispersing the para-aramid nanofibers into a uniform slurry with water under stirring conditions to obtain para-aramid nanofiber slurry.
[0022] In S2, the washing is performed using a continuous countercurrent belt washer.
[0023] In S2, the washing is performed with water.
[0024] In S2, the stirring speed is 300-1000 r / min, and the stirring time is 0.5-2 h.
[0025] In step 1, the perfluorosulfonic acid solution is a mixture of perfluorosulfonic acid (PFSA) and a first solvent, and the first solvent is one or a mixture of several of N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, acetone and ethanol.
[0026] In step 1, the method for obtaining a perfluorosulfonic acid solution comprises: mixing perfluorosulfonic acid (PFSA) and a first solvent, reacting at 100 to 200° C. for 3 to 6 hours, and obtaining a perfluorosulfonic acid solution.
[0027] Step 2, preparing a wet paper sheet from the composite solution by a papermaking method, dehydrating and drying to obtain a composite layer (middle layer);
[0028] In step 2, a vacuum pressure of 0.05-0.5 MPa is set for the composite solution when forming a wet paper sheet.
[0029] In step 2, the dehydration is performed by squeezing with a squeezing roller.
[0030] In step 2, the drying includes: first drying at 105-115° C. for 20-40 minutes, and then drying at 145-155° C. for 5-30 minutes.
[0031] Step 3, coating the perfluorosulfonic acid solution on both sides of the composite layer, allowing it to stand, and drying it to obtain a composite proton exchange membrane.
[0032] In step 3, the standing time is 10 to 20 minutes.
[0033] In step 3, the drying temperature is 60-120° C., and the drying time is 5-10 hours.
[0034] In step 3, the coating method is one of cast coating, blade coating and spray coating, preferably cast coating.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention combines perfluorosulfonic acid and para-aramid nanofibers by a papermaking method to obtain a composite layer, and coats perfluorosulfonic acid solution on both sides of the composite layer to obtain a composite proton exchange membrane, thereby improving the thermal stability, dimensional stability, mechanical strength and swelling resistance of the proton exchange membrane while ensuring high proton conductivity, and also has the advantage of reducing hydrogen permeability. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0038] The raw material information involved in the following examples is as follows:
[0039] Poly(p-phenylene terephthalamide) (PPTA) is a typical aromatic polyamide with excellent properties such as ultra-high strength, high temperature resistance, acid and alkali resistance, light weight, insulation, anti-aging and long life cycle.
[0040] Perfluorosulfonic acid (PFSA) is the strongest solid superacid known to date, with the characteristics of good heat resistance, chemical stability and high mechanical strength.
[0041] Swelling rate in water: After drying, cut the film into 5cm×5cm films, and the diagonal length of the test is recorded as D d Place it in deionized water and soak it at room temperature for 24 hours. Take it out after 24 hours and measure the diagonal length after soaking as D w , swelling ratio in water Δ D The calculation formula is as follows:
[0042] Δ D =(D w -D d ) / D d ×100%
[0043] Tensile strength: Use an electronic universal testing machine to test the tensile strength and tensile strain of the film. Cut the sample into 15mm*100mm strips and place them in the experimental fixture so that the longitudinal axis of the sample coincides with the center line of the upper and lower fixtures, and clamp them. Set the tensile speed to 10mm / min, start the experiment, and end the test after the film breaks. According to the tensile stress-strain curve and the initial thickness and width data of the film sample, calculate the tensile strength of the film according to the following formula:
[0044] σ=F / (b*d), where: σ——tensile strength, in megapascals (MPa); F——maximum load, in Newtons (N); b——sample width, in millimeters (mm); d——sample thickness (obtained by a thickness gauge), in millimeters (mm).
[0045] Proton conductivity (proton conductivity): The proton conductivity of the membrane was measured using AC impedance, and the proton conductivity of the membrane was measured at 60° C. and 100 RH%.
[0046] Thermal stability analysis: The thermal stability of the membrane was tested using a thermogravimetric analyzer in a nitrogen environment with a heating rate of 10°C / min and a temperature test range of 30-800°C.
[0047] In the following examples, water is deionized water.
[0048] Examples 1 to 3
[0049] A composite proton exchange membrane has a layered structure, which comprises an upper layer (perfluorosulfonic acid polymer layer), an intermediate layer (composite layer) and a lower layer (perfluorosulfonic acid polymer layer) from top to bottom. The upper layer, the intermediate layer and the lower layer have the same area. The upper layer comprises perfluorosulfonic acid (PFSA), the intermediate layer comprises para-aramid nanofiber and perfluorosulfonic acid, the lower layer comprises perfluorosulfonic acid (PFSA), the thickness of the composite proton exchange membrane is Aμm, the thickness of the intermediate layer is Bμm, the thickness of the upper layer is Cμm, the thickness of the lower layer is Dμm, and the ratio of the para-aramid nanofiber to the perfluorosulfonic acid in the intermediate layer is X by mass.
[0050] The method for preparing the composite proton exchange membrane comprises the following steps:
[0051] Step 1, under stirring conditions (stirring speed is 500r / min), the para-aramid nanofiber slurry and the perfluorosulfonic acid solution are mixed until uniform, to obtain a composite solution, wherein the para-aramid nanofiber slurry is a mixture of para-aramid nanofibers and water, the perfluorosulfonic acid solution is a mixture of perfluorosulfonic acid (PFSA) and a first solvent, and the ratio of the para-aramid nanofibers in the para-aramid nanofiber slurry to the perfluorosulfonic acid in the perfluorosulfonic acid solution is Y by weight, the para-aramid nanofibers in the para-aramid nanofiber slurry are 6wt%, and the content of perfluorosulfonic acid in the perfluorosulfonic acid solution is 5wt%;
[0052] Step 2, the composite solution is transferred into the material box of the paper machine, the vacuum pressure is set to 0.3 MPa, the liquid of the composite solution in the material box of the paper machine is extracted, and a wet paper sheet (wet composite layer) is obtained at the bottom of the material box, and the wet paper sheet is squeezed and dehydrated by a pressing roller, and dried in a drying cylinder: first dried at 110° C. for 30 minutes, and then dried at 150° C. for 10 minutes to obtain a composite layer;
[0053] Step 3, using a cast coating method to coat the perfluorosulfonic acid solution (the perfluorosulfonic acid solution in step 3 is the same as the perfluorosulfonic acid solution in step 1) on both sides of the composite layer, let it stand for 15 minutes to allow the perfluorosulfonic acid solution to fully infiltrate, move it to a suspended vacuum drying oven and dry it at 80°C for 8 hours to obtain a composite proton exchange membrane.
[0054] The method for obtaining para-aramid nanofiber slurry comprises the following steps:
[0055] S1, mixing a para-aramid polymer (poly(p-phenylene terephthalamide, PPTA)) and a coagulant, stirring at a speed of 600 r / min for 2 h to break up the para-aramid polymer, homogenize, and obtain a macroscopically uniform para-aramid nanofiber dispersion containing para-aramid nanofibers, wherein the ratio of the para-aramid polymer to the coagulant is 1:5 by weight, and the coagulant is a mixture of N-methylpyrrolidone and water (the ratio of N-methylpyrrolidone to water is 1:1 by weight);
[0056] S2, using a continuous countercurrent belt washing machine to clean the para-aramid nanofibers with water, and dispersing the para-aramid nanofibers into a uniform slurry with water under stirring conditions (stirring at a speed of 800 r / min for 1.5 h) to obtain para-aramid nanofiber slurry.
[0057] The method for obtaining a perfluorosulfonic acid solution includes: mixing powdered perfluorosulfonic acid (PFSA) and a first solvent, reacting in a reactor at 150° C. for 4 hours (so that the perfluorosulfonic acid is fully dissolved in the first solvent), and obtaining a perfluorosulfonic acid solution, wherein the first solvent is N-methylpyrrolidone.
[0058] The values of A, B, C, D, X and Y are shown in Table 1.
[0059] Table 1
[0060] Example A(μm) B(μm) C(μm) D(μm) X Y Example 1 35.9 20 8.0 7.9 3:1 3:1 Example 2 35.6 20 7.7 7.9 1.2:0.5 1.2:0.5 Example 3 36.1 20 8.1 8.0 0.9:0.5 0.9:0.5
[0061] Comparative Example 1
[0062] A proton exchange membrane is the composite layer in Example 1. The thickness of the proton exchange membrane in Comparative Example 1 is 21 μm.
[0063] Comparative Example 2
[0064] A proton exchange membrane is substantially the same as the composite proton exchange membrane in Example 1, except that the intermediate layer is different. The method for obtaining the intermediate layer of Comparative Example 2 is as follows: the para-aramid nanofiber slurry in Example 1 is moved into a material box of a papermaking machine, the vacuum pressure is set to 0.3 MPa, the liquid of the para-aramid nanofiber slurry in the material box of the papermaking machine is extracted, and a wet paper sheet is obtained at the bottom of the material box, and the wet paper sheet is squeezed and dehydrated by a pressing roller, and dried in a drying cylinder: first dried at 110° C. for 30 minutes, and then dried at 150° C. for 10 minutes, to obtain the intermediate layer of Comparative Example 2. The thickness of the proton exchange membrane in Comparative Example 2 is 36 μm, the intermediate layer is 20 μm, and the upper and lower layers are both 8 μm.
[0065] Comparative Example 3
[0066] A proton exchange membrane is substantially the same as the composite proton exchange membrane in Example 1, except that the intermediate layer is different. The method for obtaining the intermediate layer of Comparative Example 3 is as follows: pour the perfluorosulfonic acid solution in Example 1 into a membrane pool, put it into an oven and level it, and then dry it in the oven: first dry it at 80°C for 8 hours, then dry it at 120°C for 1.5 hours, take the membrane pool out of the oven, and peel the membrane from the membrane pool after cooling to obtain the intermediate layer of Comparative Example 3. The proton exchange membrane in Comparative Example 3 has a thickness of 36 μm, the intermediate layer is 20 μm, and the upper and lower layers are both 8 μm.
[0067] Table 2
[0068]
[0069] Comparative Examples 1 to 3 show that when the amount of para-aramid nanofiber added is large, the swelling rate of the composite proton exchange membrane is low, the thermal decomposition temperature (thermal stability) and tensile strength (mechanical stability) are high, the limiting current density is low, and the hydrogen permeation is small. As the proportion of perfluorosulfonic acid (PFSA) increases, the proton conductivity of the composite proton exchange membrane increases, and Example 3 has the highest proton conductivity, while other properties are good and the overall performance is optimal. Therefore, the present invention combines para-aramid nanofibers with PFSA to ensure that the thermal stability and mechanical stability of the proton exchange membrane are improved and the hydrogen permeability is reduced under the premise of ensuring high proton conductivity.
[0070] Comparative analysis of Example 1 and Comparative Example 1 shows that the composite proton exchange membrane has a layered structure, and the addition of perfluorosulfonic acid in the upper and lower layers is beneficial to increasing the proton conductivity and can reduce the hydrogen permeation to a certain extent.
[0071] Comparative analysis of Example 1 and Comparative Example 2 shows that the addition of perfluorosulfonic acid in the intermediate layer is beneficial to significantly improve the proton conductivity.
[0072] Comparative analysis of Example 1 and Comparative Example 3 shows that the composite proton exchange membrane has a layered structure, and the addition of para-aramid nanofibers in the middle layer is beneficial to improving the dimensional stability, thermal stability and mechanical stability of the proton exchange membrane, while reducing the hydrogen permeation.
[0073] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A composite proton exchange membrane, characterized in that: The composite proton exchange membrane is a layered structure, which comprises an upper layer, a middle layer and a lower layer from top to bottom. The upper layer comprises perfluorosulfonic acid, the middle layer comprises para-aramid nanofibers and perfluorosulfonic acid, and the lower layer comprises perfluorosulfonic acid.
2. The composite proton exchange membrane according to claim 1, characterized in that: The composite proton exchange membrane has a thickness of 20 to 60 μm, the middle layer has a thickness of 15 to 30 μm, the upper layer has a thickness of 5 to 10 μm, and the lower layer has a thickness of 5 to 10 μm.
3. The composite proton exchange membrane according to claim 1, characterized in that: In terms of mass fractions, the ratio of the para-aramid nanofibers to the perfluorosulfonic acid in the middle layer is (0.1-5.0):(0.04-2.0).
4. The composite proton exchange membrane according to claim 1, characterized in that: The upper layer, the middle layer and the lower layer have the same area.
5. A method for preparing a composite proton exchange membrane, characterized in that: The following steps are involved: Step 1, under stirring conditions, mixing a para-aramid nanofiber slurry and a perfluorosulfonic acid solution until uniform, to obtain a composite solution, wherein the para-aramid nanofiber slurry includes para-aramid nanofibers, the perfluorosulfonic acid solution includes perfluorosulfonic acid, and the ratio of the para-aramid nanofibers in the para-aramid nanofiber slurry to the perfluorosulfonic acid in the perfluorosulfonic acid solution is (0.1-5.0): (0.04-2.0) by weight; Step 2, preparing a wet paper sheet from the composite solution by a papermaking method, dehydrating and drying to obtain a composite layer as the intermediate layer; Step 3, coating the perfluorosulfonic acid solution on both sides of the composite layer, allowing it to stand, and drying it to obtain a composite proton exchange membrane.
6. The preparation method according to claim 5, characterized in that: In step 1, the para-aramid nanofiber slurry contains 0.01 to 10 wt % of the para-aramid nanofiber.
7. The preparation method according to claim 5, characterized in that: In step 1, the content of perfluorosulfonic acid in the perfluorosulfonic acid solution is 3-6 wt %.
8. The preparation method according to claim 5, characterized in that: In step 2, a vacuum pressure of 0.05-0.5 MPa is set for the composite solution when forming a wet paper sheet.
9. The preparation method according to claim 5, characterized in that: The method for obtaining para-aramid nanofiber slurry comprises the following steps: S1, mixing a para-aramid polymer and a coagulant, stirring, to obtain a para-aramid nanofiber dispersion containing para-aramid nanofibers, wherein the ratio of the para-aramid polymer to the coagulant is 1:(2-10) by weight; S2, washing the para-aramid nanofibers, and dispersing the para-aramid nanofibers into a uniform slurry with water under stirring conditions to obtain para-aramid nanofiber slurry.
10. The preparation method according to claim 9, characterized in that: The coagulant is the first substance, the second substance or water, the second substance is a mixture of water and the first substance, and the first substance is N-methylpyrrolidone, methanol and / or ethanol.
Citation Information
Patent Citations
PVDF (polyvinylidene fluoride) modified perfluorosulfonate proton exchange membrane and preparation method thereof
CN104558649A
Cited By
Hard-water-resistant multilayer composite proton exchange membrane as well as preparation method and application thereof
CN120854592A
Enhanced composite proton exchange membrane based on hydrophobic phase modification and preparation method thereof
CN121506988A